A cascade of multiple complications hampering a complex high‐risk percutaneous coronary intervention (CHIP‐PCI): When ingenuity overcomes troubles!. Issue 12 (26th October 2020) - Marchese, Alfredo; Tito, Antonio; Paparella, Domenico; Colombo, Antonio
Abstract: Even skilled CHIP operators can run into multiple complications. Some are unexpected and not related to the operator, and others are fully preventable by careful procedural choices. If those occur, the knowledge of devices and cognitive skills become lifesaving elements and sudden issues need to be dealt with calmly and efficiently. Abstract : Even skilled CHIP operators can run into multiple complications. Some are unexpected and not related to the operator, and others are fully preventable by careful procedural choices. If those occur, the knowledge of devices and cognitive skills become lifesaving elements and sudden issues need to be dealt with calmly and efficiently.